The journal of cardiovascular computed tomography: A year in review: 2022 - Pontone, Gianluca; Mushtaq, Saima; Al'Aref, Subhi J.; Andreini, Daniele; Baggiano, Andrea; Canan, Arzu; Cavalcante, Joao L.; Chelliah, Anjali; Chen, Marcus; Choi, Andrew; Damini, Dey; De Cecco, Carlo Nicola; et al. (Journal of Cardiovascular Computed Tomography, 2023)
This review aims to summarize key articles published in the Journal of Cardiovascular Computed Tomography (JCCT) in 2022, focusing on those that had the most scientific and educational impact. The JCCT continues to expand; the number of submissions, published manuscripts, cited articles, article downloads, social media presence, and impact factor continues to grow. The articles selected by the Editorial Board of the JCCT in this review highlight the role of cardiovascular computed tomography (CCT) to detect subclinical atherosclerosis, assess the functional relevance of stenoses, and plan invasive coronary and valve procedures. A section is dedicated to CCT in infants and other patients with congenital heart disease, in women, and to the importance of training in CT. In addition, we highlight key consensus documents and guidelines published in JCCT last year. The Journal values the tremendous work by authors, reviewers, and editors to accomplish these contributions.
CRIS-Team Scopus Importer:2023-05-05
Keywords: CTA=coronary CT angiography; HRP=high risk plaques; TAVR=Transcatheter aortic valve replacement